Pengaruh Kinerja Lingkungan, Kepemilikan Institusional, dan Ukuran Dewan Direksi Terhadap Carbon Emission Disclosure - Nihayatuzzainia Nihayatuzzainia; Tumirin Tumirin (Jurnal Akuntan Publik, 2025)
The purpose of this research is to examine how environmental performance, institutional ownership, and board size affect carbon emission disclosure. The research sample consists of 71 companies in the energy, industrial, and agricultural sectors in 2022 listed on the Indonesia Stock Exchange (BEI). Purposive sampling method was used to collect data in this study. The data analysis technique employs multiple linear regression analysis. The results show that environmental performance has a positive effect on carbon emission disclosure, while institutional ownership and board size have do not affect on carbon emission disclosure.